Measuring informal STEM learning supports across contexts and time - Bradley J. Morris; Whitney Owens; Kirsten Ellenbogen; Sibel Erduran; John Dunlosky (SpringerOpen, 2019)
Abstract Background Informal science activities are critical for supporting long-term learning in STEM fields. However, little is known about the kinds of activities children and their families engage in outside of formal settings and how such activities foster long-term STEM engagement. One gap in the literature is the lack of data that document self-designated STEM activities and measure their impact on later engagement with learning opportunities that are distributed over time and contexts (i.e., the informal learning ecology). One reason for this gap is that there has been little measurement during the events, because using only a few measures (which can be completed briefly) may reduce psychometric validity. We developed an instrument, the STEMwhere app, to measure four informal science learning supports (interest, engagement, identity, and goal setting), across the informal learning ecology. For a period of 2 months, 26 children ages 7-14 used the app to check-in during STEM activities and answer eight questions about each activity. Results The results demonstrated that most STEM activities occurred in the home, often consisted of hands-on activities, suggesting that the family home provides more opportunity for engagement than other locations. Child interest and engagement ratings were high in all settings and activities suggesting that high situational interest was relatively common during these activities. Further, user ratings suggested relations between different learning supports. For example, increases in interest were related to increases in subsequent engagement and "fun" goals, while increases in engagement were related to increases in learning goals. By collecting participant-generated check-ins, we identified periods of increasing activity and their likely triggers, which is a novel measure we refer to as topical runs. We operationally defined a run as a pattern of check-ins that were unlikely to occur by chance and shared a topic or location. Conclusions Our results serve as both a proof-of-concept for a novel tool for measuring informal STEM activity in the wild that provides data consistent with existing measures and provide novel findings that contribute to our understanding of where and how informal science activity occurs.